From agricultural engineering and forestry engineering to biomechinfotronic engineering - Jiaqiang, Zheng; Hongping, Zhou; Youlin, Xu; Linyun, Xu (International Journal of Agricultural and Biological Engineering, 2009)
The deterioration of global environment, decreasing of biological diversity, increasing of natural disasters, exhausting of biological resources and acceleration of desertification emphasize the need to provide the human-beings with the suitable environments. Nowadays, precision agriculture and precision forestry have been emphasized to obtain the maximum output with minimum input and the least impact on the environment, so agricultural and forestry engineering systems require multi-disciplinary design groups to deal with some common interests and the concept of biomechinfotronics is needed. The word “biomechinfotronic”is introduced to describe the multidisciplinary aspects of this complex system. In the paper, the prospects, mission analysis, education system, research areas of biomechinfotronics are studied. The particular characteristics of biomechinfotronics are the synergistic integration of biological engineering with mechatronics, bioinformatics, infotronics, bioelectronics and intelligent computer systems for conducting common research and development and for recruiting and training students with wide specialties. Key words: agricultural and forestry engineering, precision agriculture, precision forestry, biomechinfotronics, multi-disciplinary, sustainable development DOI: 10.3965/j.issn.1934-6344.2009.01.072-78 Citation: Zheng Jiaqiang, Zhou Hongping, Xu Youlin, Xu Linyun. From agricultural engineering and forestry engineering to biomechinfotronic engineering. Int J Agric & Biol Eng, 2009; 2(1): 72